IIUM Geobat flying saucer: design, fabrication and testing - Omar, Ashraf Ali E. (s.n., 2012)
In this work, the first IIUM circular planform unmanned Aerial vehicle (IIUM-CPUAV), also known as Geobat flying saucer, was successfully designed, built and tested by the team from the Department of Mechanical Engineering, IIUM. The designing process started with gathering historical data and performing the conceptual design calculations. The maximum diameter and weight of IIUM-CPUAV are 1 m and 900 grams, respectively and foam was the main material used for fabrication. Flight tests were successfully conducted and IIUM-CPUAV was found to be stable. Based on the flight tests results, design modifications were carried out on the prototype to improve the stability and the performance. The final configuration of the IIUM-CPUAV was successfully tested.